The Impact of Cryptocurrency Adoption as a Legal Tender in El Salvador - Adityawardhan Gaikwad; Dr. Sushil Mavale (International Journal of Engineering and Management Research, 2021)
Cryptocurrency is taking the world by storm. It is certainly not a new technology anymore to the world. Countries all over the world are deciding on how they should treat the cryptocurrency as it directly impacts their existing ecosystem of fiat currency and how people use it. Different countries have adopted different approaches like considering it as a financial assets, securities, outright illegal or even legal tender in some countries. There are still a good number of countries which are yet to declare whether trading, using or mining it is legal or illegal. In such chaos, El Salvador is one such country which has adopted Bitcoin as a legal tender in 2021. It has been found that bitcoin adoption is expected to help their economy as GDP will probably increase after large scale adoption of Bitcoin. The electricity consumption for bitcoin mining has reached an all-time high. The environmental concerns are rising. However, El Salvador is keen on using 100% clean energy sources. El Salvador has been producing the largest amount of geothermal energy in all of Central America.